2011
DOI: 10.24230/kjiop.v24i3.457-491
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of burnout with job attitudes and turnover intention among Koreans

Abstract: Two representative job attitudes (job satisfaction and organizational commitment) and turnover intention were meta-analytically examined in relation to burnout using articles published in Korean journals. In total, 11560 employees from 42 samples were included. The results showed that the three dimensions of burnout (emotional exhaustion, depersonalization, and reduced personal accomplishment) were negatively related with job satisfaction and affective commitment and positively related with turnover intention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Burnout has been included in the 11th revision of the International Classification of Diseases (ICD-11) -effective from 2022 -by the World Health Organization (2019) and is classified as an 'occupational phenomenon' defined as 'a syndrome conceptualised as resulting from chronic workplace stress that has not been successfully managed'. The consequences of burnout have become apparent over almost half a century of research: decreased performance (Roczniewska & Bakker, 2021;Taris, 2006), impaired job satisfaction and affective commitment (Park, Nam, & Yang, 2011;Salvagioni et al, 2017), increased turnover intention, negative perceptions of quality and safety (Garcia et al, 2019;Salyers et al, 2017) and more physical and psychological distress symptoms (Salvagioni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Burnout has been included in the 11th revision of the International Classification of Diseases (ICD-11) -effective from 2022 -by the World Health Organization (2019) and is classified as an 'occupational phenomenon' defined as 'a syndrome conceptualised as resulting from chronic workplace stress that has not been successfully managed'. The consequences of burnout have become apparent over almost half a century of research: decreased performance (Roczniewska & Bakker, 2021;Taris, 2006), impaired job satisfaction and affective commitment (Park, Nam, & Yang, 2011;Salvagioni et al, 2017), increased turnover intention, negative perceptions of quality and safety (Garcia et al, 2019;Salyers et al, 2017) and more physical and psychological distress symptoms (Salvagioni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Burnout affects not only individuals but also organizations, because it increases sickness absences (e.g., Borritz, Rugulies, Christensen, Villadsen, & Kristensen, 2006), increases turnover intentions (e.g., Alarcon, 2011) and actual turnover (e.g., Young, 2015), and decreases job performance (e.g., Taris, 2006). A meta‐analytic study of Korean literature also found that burnout was strongly related to turnover intention (Park, Nam, & Yang, 2011). To further illuminate the relationship between role conflict and burnout and find a way to reduce the strength of this relationship, we tested a buffering moderator among a sample of Korean workers using a two‐wave panel design.…”
mentioning
confidence: 96%
“…JB is widely viewed as a facilitator of TI. Studies have shown that EL caused by conflict and stress increases employees’ JB, resulting in lower job motivation, satisfaction, and engagement [ 46 49 ]. Positive exchanges with the organization, superiors, and coworkers have been found to reduce employees’ EL, lowering JB and TI [ 50 ].…”
Section: Introductionmentioning
confidence: 99%